Outdoor air pollution and risk for kidney parenchyma cancer in 14 European cohorts. Issue 7 (6th January 2017) - Raaschou‐Nielsen, Ole; Pedersen, Marie; Stafoggia, Massimo; Weinmayr, Gudrun; Andersen, Zorana J.; Galassi, Claudia; Sommar, Johan; Forsberg, Bertil; Olsson, David; Oftedal, Bente; Krog, Norun H.; Aasvang, Gunn Marit; et al.
Abstract : Several studies have indicated weakly increased risk for kidney cancer among occupational groups exposed to gasoline vapors, engine exhaust, polycyclic aromatic hydrocarbons and other air pollutants, although not consistently. It was the aim to investigate possible associations between outdoor air pollution at the residence and the incidence of kidney parenchyma cancer in the general population. We used data from 14 European cohorts from the ESCAPE study. We geocoded and assessed air pollution concentrations at baseline addresses by land‐use regression models for particulate matter (PM10, PM2.5, PMcoarse, PM2.5 absorbance (soot)) and nitrogen oxides (NO2, NO x ), and collected data on traffic. We used Cox regression models with adjustment for potential confounders for cohort‐specific analyses and random effects models for meta‐analyses to calculate summary hazard ratios (HRs). The 289, 002 cohort members contributed 4, 111, 908 person‐years at risk. During follow‐up (mean 14.2 years) 697 incident cancers of the kidney parenchyma were diagnosed. The meta‐analyses showed higher HRs in association with higher PM concentration, e.g. HR = 1.57 (95%CI: 0.81–3.01) per 5 μg/m 3 PM2.5 and HR = 1.36 (95%CI: 0.84–2.19) per 10 −5 m −1 PM2.5 absorbance, albeit never statistically significant. The HRs in association with nitrogen oxides and traffic density on the nearest street were slightly above one. Sensitivity analyses among participants who did not change residence during follow‐up showed stronger associations, but none were statistically significant. Our study provides suggestive evidence that exposure to outdoor PM at the residence may be associated with higher risk for kidney parenchyma cancer; the results should be interpreted cautiously as associations may be due to chance. Abstract : What's new? Ambient air pollution is an established cause of lung cancer. It is of considerable public health interest whether air pollution also causes other cancers. A few studies indicated that air pollution might cause kidney cancer. These authors investigated a possible link between kidney parenchyma cancer and air pollution at the residence of 289, 002 participants of 14 European cohorts. They found an increased risk in association with particulate matter air pollution, although not statistically significant.